2019
DOI: 10.1097/pcc.0000000000001797
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Patterns of Healthcare Utilization After Hospitalization for Pediatric Critical Illness Due to Respiratory Failure*

Abstract: Objectives: To quantify home care needs, healthcare utilization, and 2-year mortality after pediatric critical illness due to respiratory failure, and evaluate the impact of new morbidity and abnormal function at hospital discharge on resource use and outcomes. Design: Retrospective cohort study. Setting: Quaternary care PICU. Patients: Patients less than or equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 15 publications
2
46
2
2
Order By: Relevance
“…A recent single-center retrospective study documented that over 50% of children with critical illness due to respiratory failure were rehospitalized within 2 years of discharge, 70% of whom were readmitted to the ICU. 27 This study corroborates our findings which highlight the important morbidity faced by PARDS survivor and the pertinence of a PARDS follow-up clinic in the early detection and management of these morbidities.…”
Section: Health Resource Usesupporting
confidence: 90%
“…A recent single-center retrospective study documented that over 50% of children with critical illness due to respiratory failure were rehospitalized within 2 years of discharge, 70% of whom were readmitted to the ICU. 27 This study corroborates our findings which highlight the important morbidity faced by PARDS survivor and the pertinence of a PARDS follow-up clinic in the early detection and management of these morbidities.…”
Section: Health Resource Usesupporting
confidence: 90%
“…The majority of children experiencing a pediatric critical illness require follow-up care after discharge. 1,2 Children after a critical illness can develop posttraumatic stress disorder (PTSD), behavioral issues, cognitive changes, new morbidities, and new home healthcare needs. 1,[3][4][5][6][7][8][9] Follow-up care often includes a combination of primary care and specialty care provider visits to address these physical and emotional needs after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Children after a critical illness can develop posttraumatic stress disorder (PTSD), behavioral issues, cognitive changes, new morbidities, and new home healthcare needs. 1,[3][4][5][6][7][8][9] Follow-up care often includes a combination of primary care and specialty care provider visits to address these physical and emotional needs after discharge. Prior data have shown that more children are recommended to see a specialist after discharge rather than a primary care provider, with the leading specialists that patients are referred to being pulmonologists, physical and occupational therapists, otolaryngologists, and cardiologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without prompt intervention, ARF is associated with significant morbidity and mortality [2]. Single center cohort studies have shown that many children among the ARF survivors develop pulmonary dysfunction at discharge (PDAD) [5,6]. Respiratory infections and direct lung injury are the most common causes of ARF in children [4].…”
Section: Introductionmentioning
confidence: 99%